La Mafia e l’agire sociale delle donne - Gammaitoni, Milena (Comparative Cultural Studies: European and Latin American Perspectives, 2023)
The article presents a historical-social excursus on the criminality of women and on the stereotypes and prejudices that have long obscured a real understanding of the phenomenon: in the history of ideas, in medicine, in jurisprudence, in the media and in the various social representations. Analyzing their different roles, from the socialization of children to the mafia mentality, but also the central role of some women in the rebellion against the mafia, is a necessary path for a deeper reflection of the phenomenon.